Status of the CEPC Project - Gao Jie (EPJ Web of Conferences)
In this article we give a brief historical review of particle physics achievement through e+e- colliders and proton accelerators in the last half century and perspective for the next half century with worldwide consensus. The Circular Electron Positron Collider (CEPC) is a Higgs factory proposed by Chinese scientists in 2012, and its Technical Design Report (TDR) has been completed in Dec. 2023. Since 2024 CEPC has entered into Engineering Design Report (EDR) phase and been planned to be put into construction during China’s 15th five-year plan (2026-2030) and completed around 2035. The TDR results and EDR status and plan will be presented.